Effects of added SiO2 nanoparticles on the thermal expansion behavior of shape memory polymer nanocomposites. (January 2019) - Mahmoodi, Mohammad Javad; Hassanzadeh-Aghdam, Mohammad Kazem; Ansari, Reza
In this study, a unit cell–based micromechanical approach is proposed to analyze the coefficient of thermal expansion of shape memory polymer nanocomposites containing SiO2 nanoparticles. The interphase region created due to the interaction between the SiO2 nanoparticles and shape memory polymer is modeled as the third phase in the nanocomposite representative volume element. The influences of the temperature, volume fraction, and diameter of the SiO2 nanoparticles on the thermal expansion behavior of shape memory polymer nanocomposite are explored. It is observed that the coefficient of thermal expansion of shape memory polymer nanocomposite decreases with the increase in the volume fraction up to 12%. Also, the results reveal that with the increase in temperature, the shape memory polymer nanocomposite coefficient of thermal expansion linearly increases. The role of interphase region on the thermal expansion response of the shape memory polymer nanocomposite is found to be very important. In the presence of interphase, the reduction in nanoparticle diameter leads to lower coefficient of thermal expansion for shape memory polymer nanocomposite, while the variation of nanoparticles diameter does not affect the coefficient of thermal expansion in the absence of interphase. Based on the simulation results, the shape memory polymer nanocomposite coefficient of thermal expansion decreases as the interphase thickness increases. In addition, the contribution of interphase coefficient of thermal expansion to the shape memory polymer nanocomposite coefficient of thermal expansion is more significant than that of interphase elastic modulus.